A Study of the Prevalence of Cytotoxic and Non-Cytotoxic Klebsiella oxytoca Fecal Colonization in Two Patient Populations - Stephen A Smith; Sarah J Campbell; Duncan Webster; Michael Curley; Desmond Leddin; Kevin R Forward (Canadian Journal of Infectious Diseases and Medical Microbiology)
BACKGROUND: Klebsiella oxytoca is a cause of antibiotic-associated hemorrhagic colitis. Few reports of the occurrence of K oxytoca within stool exist and there is no gold standard method for its isolation.